Developing Physical Axiomatics: Results and Outcomes - Astafurova Maria (EPJ Web of Conferences, 2019)
The ideology and scheme of physical axiomatics are proposed, the initial postulates and axioms are formulated. The essential principles of axiomatics are based on scientific statements and concepts that reflect the fundamental properties of the physical world. One of the obtained outcomes is the statement: “In the physical world, all homogeneous quantities are commensurable, and every real physical property is limited by a certain , The analysis of the problem of incommensurability of radius and circumference leads to the conclusion about the existence of a fundamental property of the physical world, different from space and time. This property is manifested in the forms of electric charges, electric and magnetic fields, electromagnetic waves and fields. Given the nature of its manifestation, this property is called the “electromagnetic property”. The developed axiomatic system and the obtained consequences are the basis of the working model of the physical vacuum. On the basis of this model there have been derived the equations connecting parameters of basic interactions. The components of the internal energy of the physical vacuum are determined. One of these components determines the phenomenon of the Universe expansion. characteristic for this property, minimum nonzero value”. Homogeneous quantities are quantities of one and the same nature, relating to the manifestation of one and the same physical property.